An exploration of faculty perspectives towards interprofessional education and collaborative practice during international electives in health professions training institutions in Africa - Faith Nawagi; Ian Guyton Munabi; Andre Vyt; Sarah Kiguli; Aloysius Gonzaga Mubuuke (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Faculty perspectives are key drivers of learning during international electives (IEs). However, in Africa, there is limited literature on these perspectives on interprofessional education and collaborative practice (IPECP) during IEs. Therefore, this study explored faculty perspectives toward IPECP within an international elective context from selected African institutions. # Methods This was an exploratory qualitative study. The study participants included faculty from four health professional training universities in Africa. Thematic analysis was used to analyze the data. Common codes were identified and grouped to create subthemes and major themes. # Results Four themes were identified: (i) The importance of IPECP during IEs, (ii) Approaches to IPECP during IEs, (iii) Perceived key barriers, and (iv) Perceived institutional support for IPECP during IEs. Most of the participants perceived IEs as a platform that can be used to cultivate IPECP with a multicultural perspective while promoting cross-border partnerships to advance health care. Suggested teaching approaches included case studies, joint clinical ward rounds, and simulations, among others, with an openness to having an online, blended, or physical mode of delivery. A framework to guide the implementation of IPECP during IEs was considered important, and most participants thought that their institutions had the infrastructure to support IPECP-IEs. # Conclusions Faculty reported enabling perspectives of IPECP during IEs, emphasizing the need for a framework to guide and structure implementation. IPECP-IEs were perceived as a unique platform to cultivate IPECP skills with a multicultural component.